Staphylococcus aureus is More Prevalent in Retail Beef Livers than in Pork and other Beef Cuts - Abdalrahman, Lubna S. (Pathogens, 2015)
Staphylococcus aureus is one of the top five pathogens contributing to acquired foodborne illnesses causing an estimated quarter million cases every year in the US. The objectives of this study were to determine the prevalence of Methicillin Susceptible S. aureus (MSSA) and Methicillin Resistant S. aureus (MRSA) in retail beef livers, beef, and pork meats sold in Tulsa, Oklahoma and to characterize the recovered strains for their virulence and antimicrobial resistance. Ninety six chilled retail beef (50 beef livers and 46 beef other cuts), and 99 pork meat samples were collected. The prevalence in beef livers was 40/50 (80%) followed by other beef cuts 23/46 (50%) then pork 43/99 (43.3%). No isolates were positive for MRSA since none harbored the mecA or mecC gene. A total of 334 recovered S. aureus isolates (143 beef livers, 76 beef, and 115 pork isolates) were screened for their antimicrobial susceptibility against 16 different antimicrobials and their possession of 18 different toxin genes. Multidrug resistance was more prevalent in the pork isolates followed by beef then beef livers. The prevalence of enterotoxin genes such as seg, seh, and sei and the toxic shock syndrome gene tst was higher in the pork isolates than in the beef ones. The hemolysin genes, particularly hlb, were more prevalent in isolates from beef livers. Molecular typing of a subset of the recovered isolates showed that they are highly diverse where spa typing was more discriminatory than PFGE. The alarmingly high incidence of S. aureus in retail beef livers in this study should raise awareness about the food safety of such meat products.